(untitled) (UNIZIK Journal of Marketing, 2026)
This study examined the influence of Facebook advertising on customers’ patronage intention of retail businesses in South-East Nigeria, focusing on four core constructs: product information, social interaction, entertainment, and perceived usefulness. The main objective was to determine how these advertising dimensions shape customers’ intention to patronize retail offerings promoted via Facebook. A descriptive survey design was adopted, with the population comprising Facebook users who follow or engage with retail business pages in the region. Out of 325 questionnaires, 208 were correctly completed and returned, yielding a response rate of 64.07%. Data analysis involved descriptive statistics, normality tests, reliability and validity checks, and multiple regression using SPSS. Findings revealed that all four variables significantly and positively influenced patronage intention: product information (β = 0.236, p < 0.001), social interaction (β = 0.185, p = 0.001), entertainment (β = 0.222, p < 0.001), and perceived usefulness (β = 0.241, p < 0.001). Together, they explained 55.1% of the variance (R² = 0.551). The study recommends that retail businesses in South-East Nigeria design integrated, audience-tailored Facebook advertising strategies that emphasize product information, promote user interactivity, incorporate entertainment, and highlight functional value to enhance customers’ engagement, trust, intent and patronage.